Performance Assessment of Kembang Merbabu Employees - Lailatul Nuraini; Agus Sugiarto (PT Mattawang Mediatama Solution, 2023)
This research aims to investigate the working conditions at Omah Kembang Merbabu and the process and benefits of employee performance evaluation in the company. The research method used is structured interviews with employees at Omah Kembang Merbabu as the primary source of information. The interviews were conducted face-to-face using a pre-arranged set of structured questions. Based on the interview findings, it can be concluded that the working conditions at the company are considered good and emphasize a sense of family in the workplace. The Standard Operating Procedures (SOP) implemented at the company are not significantly different from those in other places, which prioritize discipline and orderliness. Employee performance evaluation at Omah Kembang Merbabu is conducted through both vertical and horizontal assessments, considering important aspects such as performance standards, neatness and attitude, discipline, responsibility, and loyalty